Pengaruh Likuiditas, Leverage, dan Profitabilitas terhadap Financial Distress pada Perusahaan di Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Rini Ristanti; Hari Nurweni (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This research was conducted to examine the effect of Liquidity, Leverage and Pfitability on Financial Distress. Meanwhile, Liquidity is proxied by Current Ratio (CR), Leverage is proxied by Debt to Equity Ratio (DER), Profitability is proxied by Return On Assets (ROA), and Financial Distress is proxied by Interest Coverage Ratio (ICR). The population in this research is property and real estate companies listed on the Indonesia Stock Exchange for the 2018- 2020 period. The mechanism for collecting research samples applies purposive sampling, the total sample in this research is 21 companies with a total of 63 exploratory materials. The data analysis method applied is panel data regression estimation, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression, F test, t test, coefficient of determination. Regarding the conclusions of this study, it proves that Liquidity has a significant positive impact on Financial Distress, Leverage has a significant negative impact on Financial Distress, and Profitability has a significant positive impact on Financial Distress.